Global tourism in crisis: conceptual frameworks for research and practice. Issue 3 (16th September 2021) - Cheer, Joseph M.; Lapointe, Dominic; Mostafanezhad, Mary; Jamal, Tazim
Abstract : Purpose: The aims of this Editorial are twofold: (i) synthesise emergent themes from the special issue (ii) tender four theoretical frameworks toward examination of crises in tourism. Design/methodology/approach: The thematic analysis of papers highlights a diversity of COVID-19 related crises contexts and research approaches. The need for robust theoretical interventions is highlighted through the four proposed conceptual frameworks. Findings: Crises provides a valuable seam from which to draw new empirical and theoretical insights. Papers in this special issue address the unfolding of crises in tourism and demonstrate how its theorization demands multi and cross-disciplinary entreaties. This special issue is an invitation to examine how global crises in tourism can be more clearly appraised and theorised. The nature of crisis, and the extent to which the global tourism community can continue to adapt remains in question, as dialogues juxtapose the contradictions between tourism growth and tourism sustainability, and between building back better and returning to normal. Originality/value: The appraisal of four conceptual frameworks, little used in tourism research provides markers of the theoretical rigour and novelty so often sought. Beck's risk society reconceptualises risk and the extent to which risk is manmade. Biopolitics refers to the power over the production and reproduction of life itself, where the political stake corresponds to power over society. The political ecology of crisis denaturalises "natural" disasters and their subsequent crises. Justice complements an ethic of care and values like conative empathy to advance social justice and well-being.